The Effect of Learning Motivation on Mathematics Learning Achievement of Class XI Students of SMK Negeri 2 Pematangsiantar T.A 2022/2023 - Saragih, Marikris Natalia; Siahaan, Theresia Monika; Sidabutar, Ropinus (Lembaga Riset Mutiara Akbar, 2022)
The purpose of this study was to determine whether there was an influence of learning motivation on Mathematics Learning Achievement of class XI students of SMK Negeri 2 Pematangsiantar which consisted of 30 students. This research uses quantitative research with Quasi Experimental design research method. The population in this study was class XI as many as 9 classes at SMK Negeri 2 Pematangsiantar as many as 544 students. The number of samples taken was 30 students, namely class XI TAV-2. Data collection techniques using questionnaires and pre-test and post-test. The results of the study were to determine how much influence learning motivation had on mathematics learning achievement for XI grade students of SMK Negeri 2 Pematangsiantar T.A 2022/2023. Learning achievement based on pre-test and post-test questions is high with an average score of 75.50 and 79.33